THE JOURNEY SO FAR IN SENIOR HIGH SCHOOL ENROLMENT OF GIRLS AND PERFORMANCE IN GHANA: THE CASE OF KASSENA-NANKANA EAST MUNICIPALITY - Alua, M. A.; Agalga, J.; Akamba, M. (UDS International Journal of Development, 2022)
Empowering the girl child has long been the goal of many countries especially countries hard hit by gender disparity in education. Ghana, just like other countries in sub-Saharan Africa, has implemented policies to help address gender disparity in education. This study sought to assess factors that limit female enrolment and performance despite policies and programmes put in place to solve gender disparity in education. Using a quantitative research approach, questionnaires were administered to 1,070 students and 170 teachers. Secondary data on enrolment and performance were also acquired from the Kassena-Nankana East Municipal office of the Ghana Education Service. The study revealed that though enrolment in senior high schools increased for both boys and girls from 2010/2011 to 2019/2020 academic years, girls still lagged behind boys in enrolment and performed inversely in the West African Senior School Certificate Examination. Poor parental control, peer pressure, teenage pregnancy, poverty, early marriage and betrothal, and gender roles, still have significant effects on female enrolment. Access to money for upkeep affects the concentration of girls in school while policies and programmes put in place to help address gender disparity, are riddled with limitations. The way forward is to ensure that policies meet their goals as well as encouraging girls to take education serious through initiatives such as rewarding brilliant students and enhancing mentorship in schools. Keywords: Girl child, Enrolment, Performance, Senior high school, Challenges.